Moral distress and its influential factors in the nurses of the nursing homes in khorasan provinces in 2019: A descriptive-correlational study - Ali Sedaghati; Abdolghader Assarroudi; Rahim Akrami; Mostafa Rad (Wolters Kluwer Medknow Publications, 2020)
Background: Nurses in nursing homes are constantly faced with various moral decisions in terms of elderly care, which in turn causes moral distress. This study aimed to evaluate the moral distress status and its influential factors in the nursing homes in Khorasan provinces, Iran. Materials and Methods: This descriptive-correlational study was conducted on 227 nurses engaged in the nursing homes of Khorasan provinces in 2019. The subjects were selected via census sampling. Data were collected using demographic, occupational, and care center characteristics questionnaire and a moral distress questionnaire. Data analysis was performed in SPSS version 16 using the Mann-Whitney U and Kruskal-Wallis test. Results: The mean (SD) score of moral distress was 28.68 (19.19), and 93.83% of the subjects reported low levels of moral distress. Significant correlations were observed between moral distress and age, work experience, workplace, nurse-physician relations, motivation of the nurses, care facilities, and medical equipment. Furthermore, the highest mean (SD) score of moral distress belonged to the items regarding the lack of work experience 12.19 (3.12). Conclusions: According to the results, moral distress in the nurses of the studied nursing home was relatively low. Despite the favorable outcome of the study, the age discrimination of nurses by nursing homes should not be overlooked.